When defects turn into virtues: the curious case of zirconium-based metal-organic frameworks - Marco Taddei (Coordination Chemistry Reviews, 2017)
Zirconium-based metal-organic frameworks (Zr-MOFs) are one of the most attractive classes of MOF materials, due to their superior thermal, chemical and mechanical stability. Recently, Zr-MOFs have been shown to feature an unusually high concentration of defects without suffering from severe loss of stability. This feature makes Zr-MOFs unique among MOF materials and is generating additional interest around them. Defects have a significant impact on porosity, thermal properties, mechanical properties, Lewis and Brønsted acidity. Researchers have quickly recognized that defects can be engineered to tune the physical-chemical properties of Zr-MOFs, opening up new avenues for their practical application. The scope of the present review article is to provide a comprehensive account of the progress made in this field since the discovery of defects in Zr-MOFs in 2011 and to point out some relevant controversies and open issues of fundamental nature that need to be addressed to improve the understanding of the very nature of defects.